Storage performance of forced ventilated, natural ventilated, and traditional methods on the quality of onion bulbs - Chattha, Shakeel Hussain; Mirani, Benish Nawaz; Soomro, Shakeel Ahmed; Ibupoto, Khalil Ahmed; Khan, Zaheer Ahmed (Journal of Pure and Applied Agriculture, 2023)
An experiment investigating the losses of onion bulbs occurring during the storage in different storage structures was conducted at the Department of Farm Structures, Sindh Agriculture University, Tandojam. Freshly harvested onion bulbs free from defects were collected from the local market of Nasarpur and were then placed in different storage structures (forced ventilated wooden structure, naturally ventilated wooden structure, and traditional method) for 60 days. The quality in terms of different parameters that is physiological loss in weight, rotting, sprouting and firmness were carried out at an interval of 10 days. The results showed that the storage time and storage method had a significant effect on the quality of onion bulbs. Weight loss (0-23.5%), rotting (0- 26.8%) and sprouting (0-15.2%) of onion bulbs showed an increasing trend throughout the storage period (60 days). However, firmness of the onion bulb decreased with increasing storage period (8.3 to 3.2 lbs). Forced ventilated wooden structure maintained lowest weight loss (14.8%), rotting (7.4%) and sprouting (7.8%) with highest firmness (5.6 lbs), followed by naturally ventilated wooden structure and traditional method respectively. Ambient temperature and relative humidity were lower in forced ventilated wooden structure followed by natural ventilated wooden structure and traditional method respectively. The present study concludes that forced ventilated wooden structure resulted to be better in maintaining the quality parameters of onion bulbs, the adoption of this method is strongly suggested to reduce the storage losses at farm level. © 2020 Department of Agricultural Sciences, AIOU